2018
DOI: 10.1007/s11695-018-3155-6
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Improves Hyperandrogenism, Menstrual Irregularities, and Metabolic Dysfunction Among Women with Polycystic Ovary Syndrome (PCOS)

Abstract: Bariatric surgery improves key diagnostic features seen in women with PCOS and ovarian volume, and free testosterone may have utility in predicting likelihood of metabolic benefit from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 37 publications
1
39
0
5
Order By: Relevance
“…Our research has indicated that women of reproductive age attain body weight stability at 12 months, which indicates a mesomeric state suitable for pregnancy. Previous studies have shown that, in obese women with polycystic ovary syndrome, hormones such as estrogen and progestogen achieve a normalized balance as early as 3 months after bariatric surgery, which has led to unplanned pregnancies (17). Therefore, guidelines for bariatric surgery often suggest that pregnancy be avoided during the first 18-24 months postoperatively-which is generally based on consensus instead of evidence (18).…”
Section: Discussionmentioning
confidence: 99%
“…Our research has indicated that women of reproductive age attain body weight stability at 12 months, which indicates a mesomeric state suitable for pregnancy. Previous studies have shown that, in obese women with polycystic ovary syndrome, hormones such as estrogen and progestogen achieve a normalized balance as early as 3 months after bariatric surgery, which has led to unplanned pregnancies (17). Therefore, guidelines for bariatric surgery often suggest that pregnancy be avoided during the first 18-24 months postoperatively-which is generally based on consensus instead of evidence (18).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial reductions in BMI and lipid profile were noted postoperatively (P<0.05) [31]. Patients' androgen levels also significantly decreased (P<0.05) such that the percentage meeting the criteria for hyperandrogenism and irregular menses subsequently dropped (P<0.05) [31]. However, ovarian volume (OV) was not seen as significantly declining postoperatively [31].…”
Section: Reviewmentioning
confidence: 96%
“…Christ and Falcone performed a review on 44 women with PCOS regarding the impact of bariatric surgery on metabolic and hormone levels and its predicted benefits post-operation [31]. Substantial reductions in BMI and lipid profile were noted postoperatively (P<0.05) [31].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent survey, the authors found a significant reduction of ovarian volume in severely obese women suffering from PCOS after bariatric surgery. The authors concluded that bariatric surgery improves key diagnostic features in women with PCOS and hyperandrogenism [89,90]. Another survey with a follow-up of four years confirmed the persistence of these hormonal changes.…”
Section: Sexual Hormones and Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 89%